Mesoscopic study of the effective thermal conductivity of dry and moist soil. (February 2019) - Cai, Shanshan; Zhang, Boxiong; Cui, Tengfei; Guo, Haijin; Huxford, Joe
Highlights: Provide a mesoscopic model to study the heat transfer in soil-like materials. Perform thermal probe tests to study the fractal quartz sand in mesoscopic scale. Clarify the impacts of mesoscopic structural parameters in dry and moist materials. Verify that the randomness of the porous structure does have considerable impact. Abstract: The ground heat exchanger (GHE) is a key component in the ground coupled heat pump (GCHP) system. The design of GHE significantly depends on the effective thermal conductivity of the ambient soil, which is derived from thermal response tests in the field. However, the test results normally indicate large differences in value, even at the same location. Such variations might be caused by the mesoscopic structure of soil. In order to clarify the impacts of the mesoscopic structural parameters on the effective thermal conductivity of soil-like materials, this paper presents and analyzes the findings from thermal probe tests and a modified random fractal model. It is found that porosity and degree of saturation are still the dominant factors, while the impacts of fractal dimension and size ratio are minor. The randomness of the porous structure in the soil-like materials does have considerable impact on the effective thermal conductivity.